Mercury: Empowering Programmers’ Mobile Work Practices with Microproductivity - Williams, Alex; Kaur, Harmanpreet; Iqbal, Shamsi; White, Ryen W.; Teevan, Jaime; Fourney, Adam (UIST 2019, 2019)
There has been considerable research on how software can enhance programmers’ productivity within their workspace. In this paper, we instead explore how software might help programmers make productive use of their time while away from their workspace. We interviewed 10 software engineers and surveyed 78 others and found that while programmers often do work while mobile, their existing mobile work practices are primarily exploratory (e.g., capturing thoughts or performing online research). In contrast, they want to be doing work that is more grounded in their existing code (e.g., code review or bug triage). Based on these ﬁndings, we introduce Mercury, a system that guides programmers in making progress on-the go with auto-generated microtasks derived from their source code’s current state. A study of Mercury with 20 programmers revealed that they could make meaningful progress with Mercury while mobile with little effort or attention. Our ﬁndings suggest an opportunity exists to support the continuation of programming tasks across devices and help programmers resume coding upon returning to their workspace.